The Impact of Immigrants on the Number and Type of Births - Gumusburun, Neset; Mendes, Ergun (UI Scholars Hub, 2024)
Background: Although cesarean section is a life-saving procedure in certain situations, it may result in complications for maternal and infant health when conducted, especially for nonmedical purposes. The civil war in Syria has significantly modified the demographic and ethnic structure of Turkey, which has affected the number and type of births occurring here. In this study, we aimed to determine the effect of the increasing Syrian refugee patient population on primary cesarean section rates in Kilis/Turkey. Methods: In this retrospective cohort study, pregnant women who gave birth at the State Hospital in the Kilis province in Turkiye between 2010 and 2021 were assigned to two groups: Syrian refugees and Turkish women, based on their ethnicity. The numbers, types, and rates of deliveries were separately studied for each group. Results: A total of 39,537 deliveries took place at our hospital. The 12-year total cesarean section rate was determined to be 25.5%, with the total primary cesarean section rate of 8.8%. While the most common cesarean indication was previous cesarean section, the most common primary cesarean indication was fetal distress. Conclusions: The tendency of Syrian patients to vaginal delivery, probably owing to cultural factors, has reduced the rate of primary cesarean section in Turkey.